Analysis of the oxyR-ahpC region in isoniazid-resistant and -susceptible Mycobacterium tuberculosis complex organisms recovered from diseased humans and animals in diverse localities. - Sreevatsan, S (1997)
Automated DNA sequencing was used to analyze the oxyR-ahpC region in 229 Mycobacterium tuberculosis complex isolates recently recovered from diseased humans and animals. The entire 1,221-bp region was studied in 118 isolates, and 111 other isolates were sequenced for oxyR, ahpC, or the 105-bp oxyR-ahpC intergenic region. The sample included isoniazid (INH)-susceptible and -resistant organisms in which the katG gene and inhA locus had previously been sequenced in their entirety to identify polymorphisms. A total of 16 polymorphic sites was identified, including 5 located in oxyR, 2 in ahpC, and 9 in the 105-bp intergenic region. All polymorphic sites located in the intergenic region, and the two missense substitutions identified in ahpC, occurred in INH-resistant organisms. In contrast, there was no preferential association of polymorphisms in oxyR, a pseudogene, with INH-resistant organisms. Surprisingly, most INH-resistant strains with KatG codon 315 substitutions that substantially reduce catalase-peroxidase activity and confer high MICs of INH lacked alterations in the ahpC gene or oxyR-ahpC intervening region. Taken together, the data are consistent with the hypothesis that some polymorphisms located in the ahpC-oxyR intergenic region are selected for after reduction in catalase or peroxidase activity attributable to katG alterations arising with INH therapy. These mutations are uncommon in recently recovered clinically significant organisms, and hence, there is no strict association with INH-resistant patient isolates. The ahpC compensatory mutations are apparently uncommon because strains with a KatG null phenotype are relatively rare among epidemiologically independent INH-resistant organisms.